Transient stabilization of human cardiovascular progenitor cells from human pluripotent stem cells in vitro reflects stage-specific heart development in vivo - Bolesani, Emiliano; Bornhorst, Dorothee; Iyer, Lavanya M; Zawada, Dorota; Friese, Nina; Morgan, Michael; Lange, Lucas; Gonzalez, David M; Schrode, Nadine; Leffler, Andreas; Wunder, Julian; Franke, Annika; et al. (Cardiovascular research, 2024)
Understanding the molecular identity of human pluripotent stem cell (hPSC)-derived cardiac progenitors and mechanisms controlling their proliferation and differentiation is valuable for developmental biology and regenerative medicine.Here, we show that chemical modulation of histone acetyl transferases (by IQ-1) and WNT (by CHIR99021) synergistically enables the transient and reversible block of directed cardiac differentiation progression on hPSCs. The resulting stabilized cardiovascular progenitors (SCPs) are characterized by ISL1pos/KI-67pos/NKX2-5neg expression. In the presence of the chemical inhibitors, SCPs maintain a proliferation quiescent state. Upon small molecules, removal SCPs resume proliferation and concomitant NKX2-5 up-regulation triggers cell-autonomous differentiation into cardiomyocytes. Directed differentiation of SCPs into the endothelial and smooth muscle lineages confirms their full developmental potential typical of bona fide cardiovascular progenitors. Single-cell RNA-sequencing-based transcriptional profiling of our in vitro generated human SCPs notably reflects the dynamic cellular composition of E8.25-E9.25 posterior second heart field of mouse hearts, hallmarked by nuclear receptor sub-family 2 group F member 2 expression. Investigating molecular mechanisms of SCP stabilization, we found that the cell-autonomously regulated retinoic acid and BMP signalling is governing SCP transition from quiescence towards proliferation and cell-autonomous differentiation, reminiscent of a niche-like behaviour.The chemically defined and reversible nature of our stabilization approach provides an unprecedented opportunity to dissect mechanisms of cardiovascular progenitors’ specification and reveal their cellular and molecular properties.
Veröffentlicht: 05. Juni 2024
Gesehen am 26.11.2024